Effects of cover crops on organic lettuce grown in a no-tillage system in the southern brazil amazon - Teixeira Ferreira Cândido, Aureane Cristina; da Silva Ponce, Franciely; Rodrigues, José Alesando; Felito, Ricardo Adriano; Yamashita, Oscar Mitsuo; de Carvalho, Marco Antônio Camillo; Seabra Júnior, Santino [UNESP] (My University, 2025)
The combination of organic farming and no-tillage systems can be effective for sustainable food production, particularly in the Amazon biome. The objective of this study was to evaluate effects of using cover crops in a no-tillage organic production system of lettuce, grown during the summer season in Alta Floresta Mato Grosso, Brazil. The experiment was conducted on a commercial organic vegetable production farm. The experiment consisted of 10 treatments with different combinations of cover crops: Crotalaria ochroleuca (T1); C. ochroleuca + Pennisetum glaucum (T2); C. ochroleuca + Poa annua (T3); Crotalaria spectabilis (T4); C. spectabilis + Pennisetum glaucum (T5); C. spectabilis + P. annua (T6), P. glaucum (T7); P. annua (T8); weeds (spontaneous vegetation) (T9); and bare soil (T10). Two lettuce cycles were monitored: the first November–December and the second December–January. In the first cycle, no-tillage lettuce grown on residue of C. ochroleuca, C. ochroleuca + P. glaucum, C. ochroleuca + P. annua, C. spectabilis, C. spectabilis + P. glaucum, C. spectabilis + P. annua, or P. glaucum provided productive gains in the lettuce yields. Due to the intense degradation of organic matter, in the second cycle, the growth of lettuce in treatments with cover crops was equivalent to that in no-tillage with bare soil, indicating the need for re-sowing the cover crops to ensure yield gains. The combination of C. ochroleuca and C. spectabilis with P. glaucum and/or P. annua showed promise for establishing organic no-tillage systems for lettuce in the Amazon region.
Keywords: Crotalaria sp; Lactuca sativaL; no-tillage; organic agriculture; Pennisetum glaucum; Poa annua